Communicating science - Kahlor, LeeAnn; Stout, Patricia A. (New agendas in communication., 2010)
Science communication has become increasingly popular in journalism and mass communication as the media offer more scientific and technological information to the public. This volume explores the evolution of science communication, addressing key issues and offering substance for future study. Harnessing the energies of junior scholars on the forefront of science communication, this work pushes the boundaries of research forward, allowing scholars to sample the multiple paradigms and agendas that will play a role in shaping the future of science communication. Editors LeeAnn Kahlor and Patrici.